Knowledge and Attitude Factors of Brides-to-be on the Incidence of Anemia in Pekalongan Regency - Djati, Isti Sulistyana; Nugraheni, Sri Achadi; Sriatmi, Ayun (Jurnal Locus Penelitian dan Pengabdian, 2025)
Background: Anemia remains a public health concern among prospective brides. Nutritional education plays an essential role in enhancing awareness and preventive behaviors against anemia. Methode: This quasi-experimental study applied a pretest-posttest control group design. A total of 70 prospective brides were divided into intervention and control groups. Data were analyzed using the Mann-Whitney test and logistic regression adjusted for confounding variables. Result: Significant improvements were found in knowledge, attitudes, nutrient intake, and hemoglobin levels in the intervention group compared to the control group (p=0.000). After adjusting for confounding variables, nutritional education remained significantly associated with knowledge (p=0.015), nutrient intake (p=0.010), and hemoglobin levels (p=0.005), but not with attitudes (p=0.057). Conclusion: Nutritional education effectively improves knowledge, nutrient intake, and hemoglobin levels among prospective brides, supporting its role in anemia prevention, although changes in attitude may require additional factors.